2018
DOI: 10.1159/000489459
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy Outcomes in Eyes with Tractional Diabetic Macular Edema

Abstract: Purpose: To evaluate pars plana vitrectomy (PPV) outcomes in cases with tractional diabetic macular edema (tDME). Methods: We conducted a single-center retrospective study with a follow-up of 12 months. Forty-six eyes with tDME of 38 patients submitted to PPV between 2013 and 2015 were assessed. A standard PPV was performed and surgical outcomes were registered at the 3-, 6-, and 12-month follow-up. Results: The baseline median best corrected visual acuity (BCVA) in ETDRS (Early Treatment Diabetic Retinopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Some authors suppose that long-standing macular oedema with tractional forces can easily cause MHs, with oedematous macula in particular being vulnerable to vitreous traction. 6,17 Cystoid macular edema, which may be an additional causative factor in the development of macular holes, was found in 85.7% of our cases, and the epiretinal membrane was identified in all cases preoperatively. Since we did not observe cystic changes in all cases, we suggest that tangential traction is the most important factor for MH development.…”
Section: Discussionmentioning
confidence: 67%
“…Some authors suppose that long-standing macular oedema with tractional forces can easily cause MHs, with oedematous macula in particular being vulnerable to vitreous traction. 6,17 Cystoid macular edema, which may be an additional causative factor in the development of macular holes, was found in 85.7% of our cases, and the epiretinal membrane was identified in all cases preoperatively. Since we did not observe cystic changes in all cases, we suggest that tangential traction is the most important factor for MH development.…”
Section: Discussionmentioning
confidence: 67%
“…The effect of internal limiting membrane (ILM) peeling on DME has also been investigated, and it has been found that this can result in a lower rate of recurrence following surgery [12]. The incidence of additional therapy following surgery has been reported as 6-20% in studies with a shorter follow-up [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported a case of MH that developed after intravitreal injection of bevacizumab for DME, speculating that traction by the vitreous body incarcerated at the site of insertion of the vitreous injection and change in the properties of the vitreous body by injection are involved as a trigger in the development of the MH [5]. Pessoa et al performed PPV in 46 eyes of 38 patients with DME with vitreous traction, and reported that an MH developed in 1 eye after surgery [6]. Yamamoto et al reported that there are two types of MH associated with PDR, i.e., an MH due to traction and an MH due to cystoid macular edema [7].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for diabetic macular edema (DME) includes the topical administration of steroids and anti-vascular endothelial growth factor (anti-VEGF) agents, as well as pars plana vitrectomy (PPV). However, studies have reported the development of a macular hole (MH) during the course of these treatments [1][2][3][4][5][6][7]. Here we report 2 cases of MHs that developed following anti-VEGF therapy and PPV for DME in which the MH showed the formation of a convex surface toward the vitreous cavity, unlike a typical idiopathic MH, and discuss the cause of the MH in each case.…”
Section: Introductionmentioning
confidence: 94%